Effects of incubation time and laccase concentration on immobilization of laccase on magnetic spent tea - Dg Atherah Athrisya Zainala; Mohd Syahlan Mohd Syukria (UTM Penerbit Press, 2024)
This study explores the impact of incubation time and laccase concentration on the immobilization efficiency and activity of laccase using adsorption and crosslinking method, employing magnetic spent tea as a sustainable carrier. The results indicate that the highest immobilization yield occurred at an incubation time of 24 h, achieving 96.51% immobilization yield with only 0.11 U, while the optimal enzyme activity of 4.31 U was recorded at a shorter incubation duration of 6 hours with 74.16% immobilization yield. This finding suggests that extended incubation times may enhance covalent bonding between the enzyme and the carrier but can also lead to reduced enzymatic activity due to potential over-binding. The ideal laccase concentration was identified at 1.0 mg/mL, which resulted in a notable immobilization yield of 74.16% while preserving significant enzyme activity. Higher concentrations of laccase caused steric hindrance, adversely affecting performance. Furthermore, reusability assessments revealed that the immobilized laccase's relative activity increased from 23% in the first cycle to 100% by the fifth cycle, likely facilitated by ABTS as a mediator. Utilizing magnetic spent tea not only serves as an effective and economical method for enzyme immobilization but also aids in waste reduction by transforming tea byproducts into valuable resources. This dual approach underscores the potential for enhancing enzymatic processes while advancing environmentally responsible waste management practices in biotechnological applications.